Once a Founder, Always a Founder? The Role of External Former Founders in Corporate Boards - Hendrik Terbeck; Verena Rieger; Niels Van Quaquebeke; Andreas Engelen (Journal of Management Studies, 2021)
Public corporations often appoint external former founders to their boards in hope that they will encourage a (re-)focus on creating future new business. Seeking to investigate this common practice, we integrate upper echelons theory with imprinting theory, arguing that founding a company indeed represents a formative experience that will leave an imprint on founders and their subsequent board decision-making. Subsequent to their founding experience, however, some founders may be subjected to likewise formative but public corporate experiences, for instance, by taking their own business public or by assuming CEO positions in other corporations, that will lead to a decay of the original founding imprint and its effect. We find support for our reasoning across corporate boards in S&P1500 firms ranging from 2000 to 2012.
Keywords: 650; board of directors; entrepreneurial experience; founding experience; imprinting; upper echelons theory